Electrical muscle stimulation intervention in the acute phase of neuromyelitis optica: Two case reports - Michiue, Kana (SAGE Open Med Case Rep, 2020)
The aim of this study was to examine the effect of electrical muscle stimulation on muscle atrophy caused by neuromyelitis optica. Two neuromyelitis optica patients with flaccid paralysis participated. The participants underwent a general rehabilitation program (transfer, balance, and gait training) and electrical muscle stimulation on the quadriceps femoris muscle of their paralyzed side. The change in the thickness of the vastus lateralis muscle ranged from −0.6 to 1.4 mm. These changes were minimal and did not indicate muscle atrophy. These findings suggest that in addition to general physiotherapy, electrical muscle stimulation seems safe and feasible in the acute phase of neuromyelitis optica.